Geometric applications of measure as a definite integral in mathematics education - Ďuriš, Viliam (Journal of interdisciplinary mathematics, 2020)
The paper deals with the measure as a definite integral with the implementation into the Matlab computing environment which is a very effective and modern teaching tool for solving a wide range of tasks quickly. The use of this program environment in the pedagogical process was the subject of research, which we carried out on an experimental group of students in assigned tasks from the measure theory, namely a definite integral. The main aim of our work was to present the measure theory, find and involve the appropriate modern elements in its teaching and show that the process of solving application tasks can be greatly improved and different knowledge gaps of students can be removed by using appropriate computer programs as complementary modern elements in addition to the classical approach to teaching.